2017
DOI: 10.1002/aenm.201602600
|View full text |Cite
|
Sign up to set email alerts
|

Organic Gelators as Growth Control Agents for Stable and Reproducible Hybrid Perovskite‐Based Solar Cells

Abstract: Article type: Full paperOrganic gelators as growth control agents for stable and reproducible hybrid perovskite-based solar cells Sofia Masi, [a] Aurora Rizzo, [a] Rahim Munir, [b] Andrea Listorti, [a,c] Antonella Giuri, [d] Carola Esposito Corcione, [d] Neil D. Treat, [e] Giuseppe Gigli, [a,c] Aram Amassian, [b] * Natalie Stingelin, [e,f] * and Silvia Colella* [a,c] Low molecular-weight organic gelators are widely used to influence the solidification of polymers, with applications ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
85
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 50 publications
1
85
1
Order By: Relevance
“…In recent years, in situ time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) has emerged as an effective method to monitor solid‐state thin film formation and microstructure evolution during solution casting of ink‐based semiconductors . More recently, it has also been used successfully to investigate crystallization behavior for 3D and reduced dimensional perovskites solution‐cast using spin‐coating and blade‐coating . Chen and coworkers found the coexistence of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in the intermediate phase of MAPbI 3 perovskite and accordingly fine‐tuned the quality of films by adjusting DMSO concentration to further improve solar cell performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, in situ time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) has emerged as an effective method to monitor solid‐state thin film formation and microstructure evolution during solution casting of ink‐based semiconductors . More recently, it has also been used successfully to investigate crystallization behavior for 3D and reduced dimensional perovskites solution‐cast using spin‐coating and blade‐coating . Chen and coworkers found the coexistence of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in the intermediate phase of MAPbI 3 perovskite and accordingly fine‐tuned the quality of films by adjusting DMSO concentration to further improve solar cell performance .…”
Section: Introductionmentioning
confidence: 99%
“…Chen and coworkers found the coexistence of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in the intermediate phase of MAPbI 3 perovskite and accordingly fine‐tuned the quality of films by adjusting DMSO concentration to further improve solar cell performance . We previously reported that solution‐processed MAPbI 3 and PbI 2 have a propensity to form intermediate‐ordered precursor phases, which can fully solidify into solvate co‐crystals during solution processing, as revealed by in situ diagnostics . In contrast, the addition of significant amounts of Br and Cl significantly inhibited solvate co‐crystallization, pointing to the importance of halide‐mediation in Pb‐solvent complexation .…”
Section: Introductionmentioning
confidence: 99%
“…[33,37] Subsequently, a crystalline precursor solvate formed as the solvent evaporates. When the J71 concentration was further increased to larger than 0.02%, isolated perovskite grains with J71 islands are observed with excess roughness and pinholes, leading to suppressed charge transfer and collection.…”
mentioning
confidence: 99%
“…[8] As a unique event in the landscape of solar energy harvesting, perovskite solar cells have experienced an increment of their power conversion efficiency by ≈8% (from 13.4% to 23.7%) in the last 5 years. Solutions to guarantee the durability of products are mandatory and can be numerous, if the problem is addressed from different perspectives.Within the possible approaches to stabilize the perovskite lattice and its behavior under illumination, recent efforts have focused on introducing various treatments, [11,12] molecules, or additives, [13][14][15][16][17][18][19] through different procedures. However, the well-known structural instability of hybrid perovskites under working conditions limits a real market uptake of all the related technologies.…”
mentioning
confidence: 99%
“…Within the possible approaches to stabilize the perovskite lattice and its behavior under illumination, recent efforts have focused on introducing various treatments, [11,12] molecules, or additives, [13][14][15][16][17][18][19] through different procedures. Nitrogen has been also exploited as inert species [20][21][22][23][24] but its role is still unfocused.…”
mentioning
confidence: 99%